Revealing the Relationship between Self-Esteem and Self-Concept: Revealing a Correlation Study on Catcalling Victim Women - Putri, Anggie Faradiba; Rifayanti, Rina; Ramadhani, Ayunda (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
The phenomenon of catcalling is something that can be experienced by almost most individuals in their lives, with women being most victims. This study aims to determine the relationship between self-esteem and self-concept in female victims of catcalling, a case study of late adolescence in Samarinda City. This study uses a quantitative approach. The sample in this study was 102 late adolescents who had experienced catcalling and were selected based on purposive sampling techniques. The data collection method used a scale of self-concept and self-esteem with reliability values of 0.852 and 0.863. The data analysis technique used was Pearson product moment correlation analysis. The results showed that there was a positive and significant relationship between self-esteem and self-concept in female victims of catcalling with a calculated r value = 0.540> r table 0.192 and a p value = 0.000 (p <0.050). This means that the more positive the self-concept of female victims of catcalling, the better the self-esteem they will develop towards themselves. The implications of this research are the basis for developing public policies that support education and awareness regarding the negative impacts of catcalling.Fenomena catcalling merupakan suatu yang dapat dialami oleh hampir sebagian besar individu di dalam kehidupannya, dengan wanita adalah sebagian besar dari korbannya. Penelitian ini bertujuan untuk mengetahui hubungan harga diri dengan konsep diri pada wanita korban catcalling studi kasus pada remaja akhir di Kota Samarinda. Penelitian ini menggunakan pendekatan kuantitatif. Sampel dalam penelitian ini adalah 102 remaja akhir yang pernah mengalami catcalling dan dipilih berdasarkan teknik purposive sampling. Metode pengumpulan data menggunakan skala konsep diri dan harga diri dengan nilai reliabilitas sebesar 0.852 dan 0.863. Teknik analisis data yang digunakan adalah analisis korelasi pearson product moment. Hasil penelitian menunjukkan bahwa ada hubungan yang positif dan signifikan antara harga diri dengan konsep diri pada wanita korban catcalling dengan nilai r hitung = 0.540 > r tabel 0.192 dan nilai p = 0.000 (p < 0.050). Artinya semakin positif konsep diri yang ada pada wanita korban catcalling maka semakin baik harga diri yang akan mereka kembangkan terhadap dirinya sendiri. Implikasi dari penelitian ini adalah landasan bagi pengembangan kebijakan publik yang mendukung edukasi dan kesadaran mengenai dampak negatif catcalling.